2016
DOI: 10.5713/ajas.15.1056
|View full text |Cite
|
Sign up to set email alerts
|

Lower ω-6/ω-3 Polyunsaturated Fatty Acid Ratios Decrease Fat Deposition by Inhibiting Fat Synthesis in Gosling

Abstract: The objective of the current study was to investigate the effects of dietary ω-6/ω-3 polyunsaturated fatty acid (PUFA) ratios on lipid metabolism in goslings. One hundred and sixty 21-day-old Yangzhou geese of similar weight were randomly divided into 4 groups. They were fed different PUFA-supplemented diets (the 4 diets had ω-6/ω-3 PUFA ratios of 12:1, 9:1, 6:1, or 3:1). The geese were slaughtered and samples of liver and muscle were collected at day 70. The activities and the gene expression of enzymes invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These results are likely due to the increased concentration of n-6 PUFA and decreased n-3 PUFA. A balanced ratio between n-6/n-3 can reduce fat deposition in the body by inhibiting fat synthesis ( Yu et al, 2016 ), and the index may be linked with atherosclerosis and coronary heart disease ( Milićević et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are likely due to the increased concentration of n-6 PUFA and decreased n-3 PUFA. A balanced ratio between n-6/n-3 can reduce fat deposition in the body by inhibiting fat synthesis ( Yu et al, 2016 ), and the index may be linked with atherosclerosis and coronary heart disease ( Milićević et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Broilers fed a diet supplemented with linseed oil can produce chicken meat with higher concentration of n-3 PUFA and lower n-6/n-3 ratio [ 7 ], which may benefit human health as a source of n-3 PUFA. A balanced n-6/n-3 PUFA ratios in diets could also help to decrease fat deposition by inhibiting fat synthesis [ 33 ]. Our study has demonstrated the beneficial effect of MO on health fatty acid profile of breast muscle in broilers, which may have economic benefits [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that omega-6 and omega-3 fatty acids elicit divergent effects on body fat gain through mechanisms of adipogenesis, browning of adipose tissue, lipid homeostasis, brain-gut-adipose tissue axis, and most importantly systemic inflammation [53][54][55][56]. Prospective studies clearly show an increase in the risk of obesity as the level of omega-6 fatty acids and the omega-6/omega-3 ratio increase in red blood cell (RBC) membrane phospholipids, whereas high omega-3 RBC membrane phospholipids decrease the risk of obesity.…”
Section: Risk Factorsmentioning
confidence: 99%